Euthanasia: Ethical Dilemmas Regarding Cultural Awareness - Κορναράκης (Konstantinos Kornarakis), Κωνσταντίνος (Bioethica, 2017)
This paper focuses on the anthropological background of Euthanasia’s cultural profile, claiming that a cultural reception of Euthanasia should previously deal with anthropological questions such as patient’s autonomy and its relation to existential freedom, the fear of death, the meaning of personal experience of pain in shaping one’s own freedom and the cardinal importance of community’s role in patient’s palliative care. The theological thinking can contribute in this interscientific dialogue on the end of life, re-opening the question of the ontology of person and consequently the question of eschatology.